Optimizing Flexibility in SUP9 Leaf Springs: The Synergistic Effect of Tempering Temperature and Holding Time - Kris Witono; Agustriyana, Lisa; Hadi Susilo, Sugeng (Asian Journal Science and Engineering, 2025)
This study investigates the influence of tempering temperature and holding time on the flexibility of SUP9 steel leaf springs, addressing a practical need for enhanced vibration absorption in heavy-duty vehicles operating on irregular terrain. An experimental study was conducted using a full factorial design with three temperature levels (450°C, 550°C, 650°C) and three holding times (15, 20, 25 minutes). Flexibility was quantified by measuring the maximum deflection in a three-point bending test. The results demonstrate a strong, positive correlation between the tempering parameters and flexibility. The optimal flexibility (47.76 mm deflection) was achieved at the highest treatment condition of 650°C with a 25-minute holding time, representing an 83% improvement over the least effective treatment. ANOVA results confirmed that temperature, holding time, and their interaction are all statistically significant factors (p < 0.05). These findings provide a practical, data-driven guideline for manufacturing more resilient and comfortable leaf springs by optimizing heat treatment protocols.